Crescimento pró-pobre? uma análise para os meios urbano e rural no Brasil - Ribeiro, Lilian Lopes (2015)
This paper seeks to analyze if the economic growth in Brazil has been pro-poor in its urban and rural areas. In this sense, based on census data of 2000 and 2010 were built the growth-poverty curves, proposed by Son (2004). One result of the research showed that only the center-south of the country has had a standard of growth that benefits the poor. At the state level, it was found that only ten federal units grew in favor of the less fortunate, and in for four of them, growth is a kind of trickle-down, that means that despite contributing to reduce poverty, income of rich people grew up in a larger proportion than the income of the poor. The breakdown of the sample allowed to observe also, how low is the performance of economic growth in reducing poverty, and decreasing inequality in rural areas of the country.